Cohesiveness of NGOs and the community in the anti-coastal reclamation social movement - Baharuddin, Aswin; Lubis, Adelita; Mustafa, Nurafiah; Arief, Resky Ameliyah; Gassing, Achmad Firdaus; Lubis, Mia Aulina (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This research is an elaboration of the response of the coalition of NGOs and affected communities in rejecting the sand mining in Takalar Regency, South Sulawesi. This study aims to analyze the motives and methods of advocacy carried out by NGOs and affected communities. This study also tries to examine the factors that influence cohesiveness between those who are resistant to this extractive industry. This research uses a qualitative approach. We got data in this study through interviews, observations, and document reviews. This study found that the primary motive of the Save Coastal Alliance Against the Sea Sand Mine in Takalar expresses resistance from NGOs and affected communities on the economic and environmental effects of the extractive industry of sand mining. The advocacy method adopted includes four step strategies. The first is conducting political education for citizens; Second, build alliances with other NGOs and; Third is conducting a lawsuit and; Fourth, through non-litigation. The study also found that cohesiveness between NGOs and affected communities was   the dynamics of each group internally. This has contributed to building the context of relations between NGOs and the community.